Isolation, fractionation and identification of chemical constituents from the leaves crude extracts of Mentha piperita L grown in Sultanate of Oman - Hossain, Mohammad Amzad (Asian Pacific Tropical Medicine Press, 2014)
OBJECTIVE: To analyze and identify the chemical compositions of different organic plants crude extracts of Mentha piperita (M. piperita) grown in Sultanate of Oman by gas chromatography-mass spectrometry (GC-MS). METHODS: The powder sample was extracted with methanol by using Soxhlet extractor. Methanol crude extracts of M. piperita and its derived fractions of hexane, chloroform, ethyl acetate and butanol were prepared. RESULTS: Qualitative analyses of various organic plant crude extracts of M. piperita by using GC-MS showed that majority of these compounds are bioactive. CONCLUSIONS: According to the results of the present study, the plant crude extracts could be used as medicine for the treatment of different diseases. The analysis and identification of the chemical compounds in the plant crude extracts by using GC-MS was the first time.